Penafsiran Ayat-Ayat Mutasyabihat dalam Kitab Ash-Shirat Al-Mustaqim Karya Syaikh Abdullah Al-Harari dan Implikasinya terhadap Akidah - Cahyati, Dewi; Paralihan, Hotmatua (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to analyze the mutasyabihat verse in the book Ash Shirat Al Mustaqim by Shaykh Abdullah Al Harari and its implications for the faith. This research uses a qualitative method with a literature study approach. Data was obtained from primary data sources, namely the book Ash Shirat Al Mustaqim, published by Shaykh Abdullah Al Harari in 2002, and secondary data sources, namely books and journal articles. The results of the research show that in Ash-Shirath al-Mustaqim, Shaykh Abdullah al-Harari interpreted the mutasyabihat verse using tafwidh and ta’wil methods to maintain the faith of tajsim and emphasize the principle of tanzih. For example, Istiwa’ means mastering the ‘arsh, Wajh the direction of the Qibla, Nur the giver of guidance, Yad the power of Allah, and Ja’a the signs of Allah power. This interpretation emphasizes the ability of ta’wil so that the Ahlussunnah creed is maintained, according to the word of Allah laysa kamitslihi syai’.